Effects of Graded Exergames on Fitness Performance in Elementary School Children With Developmental Coordination Disorder - Smits-Engelsman, Bouwien; Bonney, Emmanuel; Ferguson, Gillian (Frontiers in Sports and Active Living, 2021)
Developmental Coordination Disorder (DCD) is a common childhood disorder affecting movement and coordination skills, fitness, and academic performance. Increased physical fitness may have a positive influence on physical and mental health outcomes in children with DCD. Yet, little has been done to develop interventions to improve fitness performance in this group. The purpose of this study was to determine the effects of graded exergames in 7 to 12-year-old children with DCD and typically developing (TD) peers. Participants (32 DCD and 28 TD children) received a 30-min training session twice weekly for 10 weeks. Performance on motor coordination (MABC-2 test), balance, aerobic, and anaerobic fitness tests were assessed at the beginning and end of training. In addition, enjoyment and perception of exertion were measured for each participant during the training period. Both children with DCD and TD children significantly improved on motor coordination, balance, aerobic, and anaerobic fitness at the end of the training. A significant Group by Time interaction was observed on the MABC-2 total [F(1, 55) = 13.19; p < 0.001] and balance scores [F(1, 55) = 26.83; p < 0.0001], with the DCD group demonstrating larger improvements than the TD children. Both groups enjoyed the program throughout the training period even though they rated the training to be of high intensity. These findings indicate that graded exergames may serve as potential treatment for impaired fitness in children with DCD. Regular participation in graded exergames in school settings may be needed to enhance and maintain fitness performance in young children with and without DCD.